Can the Laffer curve become a policy tool for reducing tax evasion? Stratification of property tax collection by land use - Yuval Arbel; Chaim Fialkoff; Amichai Kerner (Journal of Urban Management, 2019)
We construct Laffer curves to evaluate the efficiency of local property tax collection based on a micro-level panel dataset referring to 2013-2016 and obtained from the Jerusalem municipality. Unlike previous literature, we apply a tractable ad hoc methodology, which, compared with the conventional approach, might prove to be more useful to practitioners and policy makers. Results indicate the efficiency of a tax policy designed to increase tax rates for on-sample taxpayers. According to one estimate, to preserve the same collected sum of payments as before, for the entire sample, the minimal anticipated required raise is 4.17% per annum.
Keywords: H71; R51; R52; 710; Laffer curve; Land uses; Local municipal tax